Yoga for Chronic Low Back Pain: A Meta-Analysis of Randomized Controlled Trials - Susan Holtzman; R Thomas Beggs (Pain Research and Management)
OBJECTIVES: To evaluate the efficacy of yoga as an intervention for chronic low back pain (CLBP) using a meta-analytical approach. Randomized controlled trials (RCTs) that examined pain and/or functional disability as treatment outcomes were included. Post-treatment and follow-up outcomes were assessed.